"Now there are diversities of gifts, but the same spirit." (1Cor 12:4): images of the self and concepts of office of LGBTQ* pastors in Germany. Issue 2 (4th May 2018) - Häneke, Florence
ABSTRACT: After providing background information on the legal status and admission of LGBTIAQ* pastors in Germany, the paper focusses on experiences of LGBTQ* Protestant pastors in the major German Protestant church (Evangelische Kirche in Deutschland) to explore how they include their sexual orientation and/or gender in their pastoral work. LGBTIAQ* pastors face the challenge of managing visibility and discretion, in relation to a heteronormative setting, as well as the specific expectations of LGBTIAQ* Christians. The presumption of shared experiences and knowledge by similarly marginalized people plays a part in their ministry. The paper argues that embracing those experiences and community knowledge as part of pastoral theology can strengthen their reflection on pastoral work.